Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Sockeye salmon - Pauley, Gilbert B. (U.S. Department of the Interior, 1989)
U. S. Fish and Wildlife Service. Biological report ; 82(11.116)